Канцелярія київського цивільного губернатора (1797–1917): склад, структура, повноваження - Ніколайчук, Д.О. (Проблеми історії України ХІХ – початку ХХ ст., 2017)
У статті, на основі архівних матеріалів та нормативно-правових актів
Російської імперії, що стосуються діяльності, структури канцелярії київського
цивільного губернатора та повноважень її окремих чиновників, розглянуто
організацію діяльності, управлінські механізми й визначено специфіку повноважень канцелярії київського цивільного губернатора. Встановлено, що чисельність особового складу чиновників канцелярії київського цивільного губернатора
залежала від змін у соціально-економічному та політичному житті не лише
імперії, а й Київської губернії зокрема.
У історії функціонування канцелярії київського цивільного губернатора
можемо виокремити два періоди: 1) удосконалення організаційної структури
(1797–1850-ті рр.), під час якого відбувається відновлення роботи канцелярії
цивільного губернатора й визначення повноважень чиновників канцелярії
цивільного губернатора; 2) удосконалення організаційно-правових засад діяльності (1861–1917 рр.), під час якого відбувається реформування інституту цивільного губернатора. Автором встановлено, що досвід чиновничої служби, професійні знання
отримані на різних посадах у губернській адміністрації, високий рівень кваліфікації чиновників дозволяли останнім займати одну з найвищих посад у губернській адміністрації, посівши посаду завідуючого губернаторської канцелярії. Зростаюче коло повноважень цивільних губернаторів, а відповідно і
документообігу їхніх канцелярій, обумовило стан справ, за яким завідуючі
губернаторської канцелярії у ряді випадків та за певних обставин приймали
самостійні рішення й видавали необхідні розпорядження, що зрозуміло не могло
не вплинути на питання адміністративного управління Київською губернією.
Професійні вміння цієї групи чиновників канцелярії київського цивільного губернатора мали відповідати таким діловим якостям, як: висока працездатність, відповідальність, акуратність, тямущість, практичність, знання механізму губернського управління й організації та ведення офіційного діловодства,
ділового листування. Канцелярія київського цивільного губернатора стала дієвим виконавчим
органом в системі управління Київською губернією, що здійснював організаційно-координаційні функції, забезпечуючи ефективність реалізації цивільним губернатором своїх повноважень. In the article on the basis of archival materials and legal acts of the Russian
Empire, concerning the activities, structure of the office of the Kiev civilian governor
and the powers of its individual officials, the organization of activities, management
mechanisms and specifics of the powers of the office of the Kiev civilian governor are
considered. It was established that the size of the personnel of officials of the office of
the Kiev civilian governor depended on changes in the socio-economic and political
life of not only the empire, but also the Kiev province in particular.
In the history of the office of the Kiev Civilian Governor, we can distinguish two
periods: 1) the improvement of the organizational structure (1797–1850), during
which there is a restoration of the office of the civilian governor, and was
characterized by the normalization of the powers of officials of the office of the
civilian governor; 2) improvement of the organizational and legal basis of activity
(1861–1917), During which there is a reform of the institute of the civil governor.
The author finds that the experience of the official service, professional
knowledge obtained at various positions in the provincial administration, a high level
of qualifications of officials allowed the latter to occupy one of the highest positions in
the provincial administration, having taken the position of head of the governor’s
office. The growing range of powers of civilian governors, and, accordingly, the
circulation of their offices, led to the state of affairs, under which the governors of the
governor’s office in a number of cases and under certain circumstances made
independent decisions and issued the necessary regulations, which obviously could
not but affect the issues of administrative management of the Kiev province. The
professional skills of this group of officials of the office of the Kiev civilian governor
should correspond to such business qualities as: high efficiency, responsibility, accuracy,
wisdom, practicality, knowledge of the mechanism of provincial management
and the organization and conduct of official clerical work, business correspondence.
The office of the Kiev Civilian Governor has become an effective executive body
in the management system of the Kyiv province, which carried out organizational and
coordination functions, ensuring the effectiveness of the implementation by the civilian
governor of his powers.